(untitled) (Research, Society and Development, 2020)
This study aimed to understand the role of nurses in the systematization of assistance to pregnant women, from the diagnosis of pregnancy to the implementation of nursing actions in the pregnancy process. This is an integrative review of the literature, which used the databases: SciELO, Capes Journals Portal and Google Scholar and three delimiters were used: Nursing, Nursing Assistance, and Gestation, with publication period between 2010 to 2020 in the Portuguese language. Eleven articles were selected that contemplated the role of the nurse in the gestation process, integrating the systematization of care through nursing care based on scientific evidence. As a conclusion, it was realized how important the qualified nursing assistance in the gestational process is, especially in the prenatal period, thus confirming the importance of the performance of the nursing professional.